Recanalization for long Occlusions of the Superficial Femoral Artery Prospective study about 13 cases - كنجو حسام (Latakia University Journal -Medical Sciences Series, 2023)
Endovascular treatment of femoropopliteal atherosclerotic lesions had seen a considerable expansion of its indications during the last ten years. The purpose of our study is to evaluate the effectiveness of this technique concerning long occlusion of superficial femoral artery. It is a prospective study about 13 cases of long occlusion of superficial femoral artery treated with angioplasty and stenting, which are collected in the vascular surgery department of Tichreen university hospital of Latakia , between January 2018 and Decembre 2021. The middle age of our patients is 62.2 years. We noticed a male predominance with a sex ratio H/F of 5.2 . Critical ischemia of the lower limbs with severe intermittent claudication < 200 m was the main frequent reason for consultation. All the patients benefited from the necessary explorations in order to evaluate the lesion as well as the extension of atheromatous disease. The success of the technique was obtained in 100% of the cases, without any major postoperative complication, and the average length of hospital stay was about 24 hours. The primary patency rate of the procedure was 84.6%, late thrombosis occurred in the implanted stent in two patients (15.4%), the secondary patency rate was 92.3%. The endovascular management of long occlusions of superficial femoral artery appears as an attractive solution especially in fragile patients at high surgical risk and with many comorbidities. Key words: superficial femoral artery, Obliterating arteriopathy of the lower limbs (PAD), angioplasty, stenting.